Correction: Nitrogen and sulfur co-doped porous carbon derived from human hair as highly efficient metal-free electrocatalysts for hydrogen evolution reactions. Issue 18 (14th May 2015) - Liu, Xiaojun; Zhou, Weijia; Yang, Linjing; Li, Ligui; Zhang, Zhenyuan; Ke, Yunting; Chen, Shaowei
<x xml:space="preserve">Abstract</x> Correction for 'Nitrogen and sulfur co-doped porous carbon derived from human hair as highly efficient metal-free electrocatalysts for hydrogen evolution reactions' by Xiaojun Liu et al., J. Mater. Chem. A, 2015, 3, 8840–8846.